Ex Vivo Tumor‐on‐a‐Chip Platforms to Study Intercellular Interactions within the Tumor Microenvironment. Issue 4 (5th December 2018) - Kumar, Vardhman; Varghese, Shyni
Abstract: The emergence of immunotherapies and recent FDA approval of several of them makes them a promising therapeutic strategy for cancer. While these advancements underscore the potential of engaging the immune system to target tumors, this approach has so far been efficient only for certain cancers. Extending immunotherapy as a widely acceptable treatment for various cancers requires a deeper understanding of the interactions of tumor cells within the tumor microenvironment (TME). The immune cells are a key component of the TME, which also includes other stromal cells, soluble factors, and extracellular matrix‐based cues. While in vivo studies function as a gold standard, tissue‐engineered microphysiological tumor models can offer patient‐specific insights into cancer‐immune interactions. These platforms, which recapitulate cellular and non‐cellular components of the TME, enable a systematic understanding of the contribution of each component toward disease progression in isolation and in concert. Microfluidic‐based microphysiological platforms recreating these environments, also known as "tumor‐on‐a‐chip, " are increasingly being utilized to study the effect of various elements of TME on tumor development. Herein are reviewed advancements in tumor‐on‐a‐chip technology that are developed and used to understand the interaction of tumor cells with other surrounding cells, including immune cells, in the TME. Abstract : Immunotherapy is increasingly being established as a cancer treatment. Using the immune system to target the tumor requires a deeper understanding of crosstalk between cellular and non‐cellular components in the tumor microenvironment. Tumor‐on‐a‐chip recapitulating such interactions enables the unprecedented phenotypic and mechanistic understanding of the microenvironment's role on tumor progression. This review highlights the advancements in tumor‐on‐a‐chip platform with future perspective.